PENERAPAN MEDIASI DALAM PENYELESAIAN SENGKETA TANAH OLEH BADAN PERTANAHAN NASIONAL KOTA PEKANBARU - Endah Melina; Firdaus '; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
This research is motivated increasingly high demand for land will lead to many problems arising. To ensure fairness required the public land ownership legal institutions are bound raw legal rules. Badan Pertanahan Nasional Pekanbaru is the government agency that handles issues related on land.In solving the problems of existing land disputes, Badan Pertanahan Nasional Pekanbaru promote mediation in resolving land disputes. Because solving problems of land with paths mediation resulted in a decision win win solution and promote kinship between the two parties to the dispute. With that way justice can be expected to materialize. Issues that will be examined in this study are: first, How is the implementation of mediation in Badan Pertanahan Nasional Pekanbaru? Secondly, how effectiveness of Badan Pertanahan Nasional Pekanbaru as a mediator in the settlement of a land dispute to the parties in the city of Pekanbaru? Third, What efforts should be made by Badan Pertanahan Nasional Pekanbaru in land dispute resolution with mediation in Pekanbaru city? This type of research is a sociological law research. Source of data used are primary data and secondary data, data collection techniques using interviews with 9 respondents who have and are undergoing the process of settlement of the land dispute in Badan Pertanahan Nasional Pekanbaru and conducted interview with the head section of disputes, conflicts and cases and interview with Kasub Section of Disputes, conflict and cases at Badan Pertanahan Nasional Pekanbaru and literature study.In this study the authors used a qualitative analysis, in drawing conclusions using inductive method of thinking. Results from this study were first, Through the implementation of the Land Dispute Resolution Mediation with the implementation of the research results of mediation in Badan Pertanahan Nasional Pekanbaru either. Second, The effectiveness of Badan Pertanahan Nasional Pekanbaru as a mediator in Land Dispute Resolution in Badan Pertanahan Nasional Pekanbaru has been effective to solving the problems of existing land disputes with mediation. Third, Efforts Conducted by the National Land Agency in Pekanbaru City Land Dispute Settlement in Mediation has a maximum in the resolution of existing problems. By looking at the results of the research as a whole, very precise paths promoting mediation in resolving the land dispute case.Keywords: DisputeResolution-Land-Mediation